Developing reaction time measurement tool norms for table tennis athletes - Tomoliyus Tomoliyus; Sumaryanti Sumaryanti; Hary Widodo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Table tennis coaches, athletes’ selection teams, and researchers seek a rare yet essential tool: a precise measure of reaction time performance. In this 4D research and development (R&D), the researchers aimed to develop a table tennis athletes’ reaction time (RT) measurement tool and norm the development process. Ninety participants (n=90), aged 17.97 years (99% CI: 17.7–18.2) with an average height of 168.05 cm (99% CI: 167–169), used the tool and the PLX DAQ Application recorded their data. Using RStudio and the descriptive statistics technique, we analysed the data: among key findings, the tool yielded proof of strong validity (Aiken V index = 0.92) and good reliability (ICC = 0.87). Athletes’ categorization revealed four distinct RT range boundaries: ‘Excellent’ (3 athletes), ‘Good’ (6 athletes), ‘Fair’ (50 athletes), and ‘Poor’ (31 athletes), respectively with RTs limits of 12.1 and 13.1, 14.1 and 15.1, 16.1 and 17.1, and then 18.1 and 19.1 ms. Height significantly influenced RT (r = -0.46), while age did not. As height increased from around 167.5±175 cm, RT decreased below 15 ms. We recommend disseminating a tool that is valid, reliable, and susceptible to categorising athletes’ performance.